2019
DOI: 10.1038/s41598-019-51949-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Empagliflozin on Cardiac Function, Adiposity, and Diffuse Fibrosis in Patients with Type 2 Diabetes Mellitus

Abstract: Empagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, significantly improves cardiovascular outcomes in diabetic patients; however, the mechanism is unclear. We hypothesized that empagliflozin might have beneficial effects on cardiac function, structure, adiposity, and myocardial diffuse fibrosis. This prospective study enrolled 35 patients (48.6% men, age 63.5 ± 9.7 years) with type 2 diabetes mellitus (T2DM) from June 1, 2017, to November 31, 2018. The patients received an SGLT2 inhibitor (empag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…Moreover, myocardial triglyceride content was unaffected despite its baseline value being higher in our subjects than in healthy Japanese subjects [ 37 ] or patients with left ventricular hypertrophy [ 38 ]. This result is consistent with that of a previous one-arm study showing that 6 months of empagliflozin treatment did not impact myocardial triglyceride content [ 45 ]. Considering that no clinical studies have assessed the effect of DPP-4 inhibitors on myocardial triglyceride content or compared the effects of SGLT2 inhibitors and DPP-4 inhibitors on cardiac lipid levels, this is the first study to show that SGLT2 inhibitors and DPP-4 inhibitors do not affect pericardial fat accumulation or myocardial triglyceride content at the early-stage of T2DM.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, myocardial triglyceride content was unaffected despite its baseline value being higher in our subjects than in healthy Japanese subjects [ 37 ] or patients with left ventricular hypertrophy [ 38 ]. This result is consistent with that of a previous one-arm study showing that 6 months of empagliflozin treatment did not impact myocardial triglyceride content [ 45 ]. Considering that no clinical studies have assessed the effect of DPP-4 inhibitors on myocardial triglyceride content or compared the effects of SGLT2 inhibitors and DPP-4 inhibitors on cardiac lipid levels, this is the first study to show that SGLT2 inhibitors and DPP-4 inhibitors do not affect pericardial fat accumulation or myocardial triglyceride content at the early-stage of T2DM.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy between our findings and those of previous studies might be attributed to the different study populations and increased severity of baseline heart function impairment in our study (27% of patients with an impaired baseline LVEF <50%). Nevertheless, our results are in accordance with the recent study showing that patients with T2DM with worse baseline characteristics benefit more from the SGLT2i treatment 17 . Recently, the subgroup analysis of the DECLARE–TIMI 58 indicated that SGLT2i with dapagliflozin reduced the risk of cardiovascular death or heart failure hospitalization to a greater extent in 671 patients with reduced baseline LVEF (LVEF <45%) than in those without reduced LVEF.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, our results are in accordance with the recent study showing that patients with T2DM with worse baseline characteristics benefit more from the SGLT2i treatment. 17 Recently, the subgroup analysis of the DECLARE-TIMI 58 indicated that SGLT2i with dapagliflozin reduced the risk of cardiovascular death or heart failure hospitalization to a greater extent in 671 patients with reduced baseline LVEF (LVEF <45%) than in those without reduced LVEF. This difference was driven by large reductions in cardiovascular death and all-cause mortality in patients with reduced LVEF.…”
mentioning
confidence: 99%
“…showed that improvement of diastolic function could be mediated by reduced spontaneous diastolic sarcoplasmic reticulum calcium release, independently of changes in cardiac ketone metabolism [ 39 ]. Our results are consistent with the open-label trial of Hsu et al ., who found no effect of 6 months of empagliflozin treatment on LV function, pericardial myocardial fat, myocardial fibrosis or LV mass [ 34 ]. Likewise, this study reported no effect of empagliflozin on myocardial triglyceride content at 12 weeks.…”
Section: Discussionmentioning
confidence: 99%